Critical analysis of the influence of a migration background on investment behavior in selected categorie - Krahnhof, Philippe; Frère, Eric; Zureck, Alexander (Momentum Quarterly, 2020)
This scientific article analyzes the investment behavior of people with and without a migration background in Germany. Similarities and differences in the categories “Advice on financial matters, financial products, investment goals and performance” are examined. The evaluation is based on a dataset from the isf Institute for Strategic Finance at the FOM University of Economics and Management in Essen from 2019. The standardized questionnaire comprised around 36 questions. People between the ages of 18 and 56 took part in the online survey. Above all, descriptive statistical methods were used for the evaluation. On the one hand, the study can underpin the research results from last year; on the other hand, new findings were gained in the “Financial Products” section. While there are strong similarities in the section “Advice on financial matters”, the investment goals and the selected assets differ between people in Germany with and without a migration background in the 2019 observation period.